2017
DOI: 10.4172/2168-9717.1000189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Adoption of Building Information Modeling (BIM) in the Jordanian Construction Industry

Abstract: Journal of Architectural Engineering Technology AbstractIn the last decade, construction industry has witnessed a huge transformation in term of the use of digital technologies, and particularly Building Information Modelling (BIM). BIM is a revolutionary digital technology and process that is reshaping the Architecture, Engineering and Construction (AEC) industry. Though, internationally, BIM has gained a great reputation for boosting productivity in AEC industry, but it holds undeveloped possibilities for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
2
17
0
Order By: Relevance
“…These findings concur with results obtained from similar studies such as lack of standards and codes for BIM application (Chan, 2014), and absence of government support (Matarneh & Hamed, 2017b). In their study, Matarneh & Hamed (2017a) recommend that governments should set standards and codes for BIM industry at both the hierarchical and undertaking store network level.…”
Section: Factor Analysis Of Building Information Modelling Implementasupporting
confidence: 87%
“…These findings concur with results obtained from similar studies such as lack of standards and codes for BIM application (Chan, 2014), and absence of government support (Matarneh & Hamed, 2017b). In their study, Matarneh & Hamed (2017a) recommend that governments should set standards and codes for BIM industry at both the hierarchical and undertaking store network level.…”
Section: Factor Analysis Of Building Information Modelling Implementasupporting
confidence: 87%
“…As a result, the United States of America has been recognized as a leading country in the BIM implementation, subsequently the adoption level in North America sky-rocked from twenty-eight percent to seventy-one percent within the period of 2007 and 2012, and similar experiences were reported in the United Kingdom with contractors and architects adoption level amounting to seventy-four and seventy percent respectively (McGraw-Hill, 2014). According to Matarneh and Hamed (2017), the government of the United Kingdom has a foresight of becoming the frontier of BIM in Europe; they further stated that despite the increase in the usage of BIM world-wide, the experience in relation to BIM differs from one construction to another. Singh (2017) investigated BIM adoption in developed nations and found that in Finland, BIM implementation commenced since in 2002 and by 2007, it was established that all design must be IFC certified.…”
Section: Comparative Review Of Bim Adoption: Global Contextmentioning
confidence: 99%
“…The advantages of BIM are studied in various research studies. Many researchers have identified the topmost benefits of BIM such as increased productivity and efficiency (Al-ashmori et al, 2020), visualization (Ebrahimi & Akhbari, 2015), clash detection, reduced rework during construction (Matarneh & Hamed, 2017), enhanced collaboration, and communication (Khosrowshahi & Arayici, 2012;Matarneh & Hamed, 2017), scheduling and sequencing coordination (Barlish & Sullivan, 2012). A total of 19 most relevant and significant advantages are selected for the survey and analysis of the results is carried out using descriptive statistics in SPSS.…”
Section: Benefits Of Bimmentioning
confidence: 99%
“…Barriers, such as doubts about ROI, lack vision of benefits (Eadie et al, 2014). Lack of awareness about BIM, BIM industry standards, and codes are not available (Matarneh & Hamed, 2017), and social and habitual resistance to change, traditional methods of contracting (Ahmed, 2018) are frequently observed in most of the papers. Some researchers also examined factors influencing the adoption of BIM.…”
Section: Barriers To Adoption Of Bimmentioning
confidence: 99%